(untitled) (Revista de Estudios Europeos, 2024)
This paper proposes, through the critical theory of international relations, sets out to question the functionalist and neofunctionalist theories that have traditionally dominated the investigation of European integration. The understanding of the European Union as a problem for its own and as a derivative product of late capitalism allows us to approach new transdiscplinary methodological perspectives to develop the main contemporary problem that it faces: the resistances to Europe. Additionally, proposes the assessment of European policies in a transnational way and the study of identities and perceptions as two methodological frameworks in order to provide newer conclusions to the European Studies.